(untitled) (Journal of Economic Research & Business Administration, 2016)
Today rail transport plays a key role in the economic development of virtually any country. The main function of the rail service is timely and complete the tasks necessary for the functioning of the national economy, as well as meeting the needs of the population in transportation, increasing the efficiency and productivity of the transport infrastructure. This article describes the features of rail transport in the naprimere company «KTŽ» NC JSC are the Organization of accounting and transportation in the field of railway transport. As costing services rail transport is difficult, because the technological features, IE the distance and category of cargo for carriage, as well as certain requirements are presented information. Specify actual cost accounting methods of transportation, and provides suggestions for identifying factors influencing cost services in Railway Enterprise.